Sexual coercion of married women in Nepal - Adhikari Ramesh; Tamang Jyotsna (BMC, 2010)
Abstract Background Sexual coercion is an important public health issue due to its negative association with social and health outcomes. The paper aims to examine the prevalence of sexual coercion perpetrated by husbands on their wives in Nepal and to identify the characteristics associated with this phenomenon. Methods The data used in this paper comes from a cross-sectional survey on "Domestic Violence in Nepal" carried out in 2009. A total of 1,536 married women were interviewed and associations between sexual coercion and the explanatory variables were assessed via bivariate analysis using Chi-square tests. Logistic regression was then applied to assess the net effect of several independent variables on sexual coercion. Results Overall, about three in five women (58%) had experienced some form of sexual coercion by their husbands. Logistic regression analysis found that the literacy status of women, decision-making power regarding their own health care, husband-wife age differences, alcohol consumption by the husband, and male patriarchal control all had significant associations with women's experience of sexual coercion. Literate women had 28% less chance (adjusted odds ratio (aOR) = 0.72) of experiencing sexual coercion by their husbands than did illiterate women. Women who made decisions jointly with their husbands with regard to their own health care were 36% less likely (aOR = 0.64) to experience sexual coercion than those whose health care was decided upon by their mothers/fathers-in-law. On the other hand, women whose husbands were 5 or more years older than they were more likely to report sexual coercion (aOR = 1.33) than were their counterparts, as were women whose husbands consumed alcohol (aOR = 1.27). Furthermore, women who experienced higher levels of patriarchal control from their husbands were also more likely to experience sexual coercion by their husbands (aOR = 7.2) compared to those who did not face such control. Conclusion The study indicates that sexual coercion among married women is widespread in Nepal. Programs should focus on education and women's empowerment to reduce sexual coercion and protect women's health and rights. Furthermore, campaigns against alcohol abuse and awareness programs targeting husbands should also focus attention on the issue of sexual coercion.